The body : narcissism of the media - Rutović, Željko (Array, 2020)
The popular media industry of spectacle with instruments of “seduction” produces “voluntary cosent” of man in acceptance, imitation and evaluation of distribution of corporate consumer culture. In this world man plays role beyond his ontological need and self-conscious realization of subject as thinking creature. The aim of this paper is to problematize socio-cultural phenomenology of body transfiguration, impressions and experiences in opticum of consumerist globalization. The new construction of “new” body is modeled on techniques of instrumentalisation, stereotyping and hybridization of narcissism as the primary reprezentational principle of such media experience.